MILLATLARARO OILALARNING PSIXOLOGIK XUSUSIYATLARI VA TIPOLOGIYASI - Roziqova, M.O. (SCIENCE and SOCIETY, 2024)
In this article, theoretical information about international families, inter-ethnic marriages, their socio-psychological characteristics, i.e. pre-marriage motives, family relations and their typology in these families, psychological characteristics are analyzed.